2016
DOI: 10.1007/s00220-016-2619-6
|View full text |Cite
|
Sign up to set email alerts
|

T-Duality Simplifies Bulk-Boundary Correspondence

Abstract: Abstract. Recently we introduced T-duality in the study of topological insulators. In this paper, we study the bulk-boundary correspondence for three phenomena in condensed matter physics, namely, the quantum Hall effect, the Chern insulator, and time reversal invariant topological insulators. In all of these cases, we show that T-duality trivializes the bulk-boundary correspondence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 71 publications
(140 reference statements)
1
50
0
Order By: Relevance
“…Results covering all symmetry classes in any dimension were obtained by Hannabuss, Mathai, and Thiang. In a series of papers [23,40,39], they apply the concept of T -duality to the bulk-boundary correspondence. This duality, with its origins in string theory, relates the K-theory of two torus bundles over the same base manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Results covering all symmetry classes in any dimension were obtained by Hannabuss, Mathai, and Thiang. In a series of papers [23,40,39], they apply the concept of T -duality to the bulk-boundary correspondence. This duality, with its origins in string theory, relates the K-theory of two torus bundles over the same base manifold.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ktheory of another C * -algebra called the Roe algebra, which is originally introduced by Roe [Roe88,Roe93] for the purpose of studying index theory of noncompact manifolds, is easy to handle and widely studied. A useful tool is the (equivariant) coarse Baum-Connes map [HR95,Yu97b,Sha08], which gives an isomorphism between a certain K-homology groups and K-groups of Roe algebras (note that there is another use of the Baum-Connes isomorphism in connection with the T-duality studied in [MT15a,MT15b,MT15c,HMT15]). For example, when X is a lattice of E d , the groups K * (C * (X)) are isomorphic to K d− * (pt).…”
Section: Introductionmentioning
confidence: 99%
“…Reversing the argument, this says that the extension defined by α X ⊕ ∂ X indeed correctly captures the geometry of the bulk-boundary relationship. Theorem 4.1 generalises to the hyperbolic plane geometry, the Euclidean space result [52] and the Nil and Solv geometry results [28,29]. 4.5.…”
Section: T-duality Simplifies the Bulk-boundary Correspondencementioning
confidence: 92%
“…Abstractly, such extensions may be studied using K-homology or Kasparov theoryindeed a KK-theoretic formulation was worked out in [12]. In [52,53], we showed that under appropriate T-duality transformations (a geometric Fourier transform closely related to the Baum-Connes assembly map), the Euclidean space bulk-boundary maps simplify into geometric restriction-to-boundary maps, and these results were extended to Nil and Solv geometries in [28,29].…”
Section: Introductionmentioning
confidence: 98%